2004
DOI: 10.1128/jcm.42.3.1313-1315.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between Detection Rates of Periodontopathic Bacterial DNA in Carotid Coronary Stenotic Artery Plaque and in Dental Plaque Samples

Abstract: Utilizing PCR, the 16S rRNA detection rates for Porphyromonas gingivalis, Actinobacillus actinomycetemcomitans, Bacteroides forsythus, Treponema denticola, and Campylobacter rectus in samples of stenotic coronary artery plaques were determined to be 21.6, 23.3, 5.9, 23.5, and 15.7%, respectively. The detection rates for P. gingivalis and C. rectus correlated with their presence in subgingival plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 38 publications
4
65
0
Order By: Relevance
“…Conversely to other studies, the authors did not find any periopathogens in the atheromatous plaque taken from a separate group of 27 patients. 25,26 We did not find the presence of P. gingivalis DNA in either aortic or mitral valves in a group of 60 patients (30 patients without concomitant periodontal examination), even though this DNA was detected in periodontal pockets of 15 patients. It is known that P. gingivalis possesses various properties, which can promote atherosclerosis, invade endothelial cells, and enhance atheroma formation.…”
mentioning
confidence: 81%
“…Conversely to other studies, the authors did not find any periopathogens in the atheromatous plaque taken from a separate group of 27 patients. 25,26 We did not find the presence of P. gingivalis DNA in either aortic or mitral valves in a group of 60 patients (30 patients without concomitant periodontal examination), even though this DNA was detected in periodontal pockets of 15 patients. It is known that P. gingivalis possesses various properties, which can promote atherosclerosis, invade endothelial cells, and enhance atheroma formation.…”
mentioning
confidence: 81%
“…[73] Chronic bacteremia from periodontitis may be easily happened from the daily activities e.c brushing, chewing, [73] and routine dental procedures like scaling and root planning, or the other treatments like endodontic, orthodontic and dental extraction. [74] Many studies proved that atherosclerosis plaques contained numerous periodontopathogen bacteria, [3,40,76] especially PG. [39,40] Researches have demonstrated that PG induction may invade endothel and may initiate atherosclerosis in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…[74] Many studies proved that atherosclerosis plaques contained numerous periodontopathogen bacteria, [3,40,76] especially PG. [39,40] Researches have demonstrated that PG induction may invade endothel and may initiate atherosclerosis in pigs. [75] The presences of PG in atheroma and human carotid aorta had been detected by immunostaining and PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 For example, periodontal bacteria were detected in coronary stenotic artery plaque by PCR and 16s rRNA detection, which is a component of the 30s small subunit of prokaryotic ribosomes. 58,59 It is hypothesized that bacteria penetrate into blood vessels directly and circulate through the blood stream, where at some stage bacteria invade the endothelium and make biofilm, leading to endothelial dysfunction, inflammation and atherosclerosis formation. 60 Usually, these bacteria were infected from surgery procedures, such as aortic valve implantation, and catheter insertion.…”
Section: New Target: Biofilmmentioning
confidence: 99%